More Realistic Forecasting of Future Life Events After Psilocybin for Treatment-Resistant Depression - Lyons, Taylor; Carhart-Harris, Robin Lester (Frontiers in Psychology, 2018)
Background: Evidence suggests that classical psychedelics can promote enduring changes in personality, attitudes and optimism, as well as improvements in mental health outcomes. Aim: To investigate the effects of a composite intervention, involving psilocybin, on pessimism biases in patients with treatment-resistant depression (TRD). Methods: Patients with TRD (n=15) and matched, untreated non-depressed controls (n=15) performed the Prediction Of Future Life Events (POFLE) task. The POFLE task requires participants to predict the likelihood of certain life events occurring within a 30-day period, after which the actual rate of event occurrence is reported; this gives an index of potential pessimism versus optimism bias. Psilocybin was administered in two oral dosing sessions (10mg and 25mg) one week apart. Main outcome measures were collected at baseline and one week after the second dosing session. Results: Patients showed a significant pessimism bias at baseline (t(14)=-3.260, p=0.006; 95% CI [-0.16,-0.03], g=1.1) which was related to the severity of their depressive symptoms (rs=-0.55, p=0.017). One week after psilocybin treatment, this bias was significantly decreased (t(14)=-2.714, p=0.017; 95% CI [-0.21,-0.02], g=0.7) and depressive symptoms were greatly improved (t(14)=7.900, p<0.001; 95% CI [16.17,28.23], d=1.9); moreover, the magnitude of change in both variables was significantly correlated (r=-0.57, p=0.014). Importantly, post treatment, patients became significantly more accurate at predicting the occurrence of future life events (t(14)=1.857, p=0.042; 95% CI [-0.01,0.12], g=0.6) whereas no such change was observed in the control subjects. Conclusions: These findings suggest that psilocybin with psychological support might correct pessimism biases in treatment-resistant depression, enabling a more positive and accurate outlook.